Role of coloration in antipredator strategies of Pristidactylus achalensis (Squamata: Leiosauridae) related to sex and stages of predation - Torres, María del Milagro (2021)
The interaction between behavioural and phenotypic traits, such as coloration, plays a specific role at different stages of the predatory sequence. Cryptic coloration involves a match to the background that reduces the risk of detection, and it is usually optimized by immobility behaviour. In lizards, sexual dichromatism and within-individual changes of colour can influence the level of their crypsis and thus influence antipredator behaviour and the decision to flee. Here, we examined variation in coloration and antipredator behaviour between the sexes of the Achala copper lizard (Pristidactylus achalensis). We measured sexual dichromatism and crypsis in accordance with avian vision. We also exposed lizards to a raptor dummy to assess the colour change and behaviour at the detection and approach stages of the predatory event. Finally, we tested escape behaviour in the natural habitat. We found that males were more conspicuous than females. Additionally, individuals showed distinct behaviours at different stages of the predation simulation, but there were no differences between the sexes. However, in their natural habitat males initiated flight at greater distances than females, which might be related to their more conspicuous coloration. In summary, this study shows how differences in crypsis between the sexes affect escape behaviour during the approach stage of predation.